Challenges of water supply management : a case of Umdoni Local Municipality, Kwa-Zulu Natal-South Africa - Gumbi, Ntokozo (My University, 2017)
The aim of the study was to examine the challenges of water supply management in Umdoni Local Municipality. Two methods were employed to collect data in the study. The first method involved one-on-one interviews with the participants. An interview guide was used to obtain data pertaining water supply services from a water services manager, a municipal manager and ten (10) ward councillors. The second method entailed analysis of documents within the municipality. In this study findings were based on issues such as prioritization of effective water supply for Umdoni Local Municipality, community consultation and participation, addressing capacity constrains in the Municipality such as human resources, water service infrastructure and skills development. The underlying causes of the water supply problems are based on the basic infrastructure, provision of water supply being very poor and dismal across the area. Water serves as a basic need to which everybody has the right to access, however, water supply is unfortunately disrupted by many factors. The findings in this study shows that poor water supply emanates from many factors such as management skills, technical challenges and illegal connections. This study recommends that Umdoni Local Municipality has additions of water plants, building of new reservoirs and upgrades of water pipes, especially in Amahlongwa area as it needs urgent attention.
Thesis (M. Dev.) -- University of Limpopo, 2017
Keywords: Potable water; Free basic water; Water management; Water-supply, Rural -- South Africa -- Kwa-Zulu Natal.; Water-supply -- Management; Municipal water supply -- South Africa -- Kwa-Zulu Natal.